The Application of The Socrates Learning Method to Improve Student Dialelectics in Class V PKn Lessons at SDN 01 Rantau Selatan - Mardiana Putri, Yuni (Journal of General Education Science, 2023)
Education is all knowledge about learning that occurs throughout life in all places and situations that have a positive impact on the growth of each individual. Learning activities are the core of all educational processes in schools. Learning activities occur through interaction between the teacher and students to achieve learning objectives. The learning method that is able to facilitate students to be dialectic is the Socratic methodbecause it provides many opportunities to develop students' thinking skills through a question-and-answer process. The purpose of this research is to find out whether the Socratic learning method can improve dialectics and to find out how the Socratic learning method is applied to Citizenship Education in Class V SDN 01 Rantau Selatan. This research is a class action research (classroom action research). The application of the Socratic method can improve the Dialectics of Class V Students of SD Negeri 01 Rantau Selatan. The successful application of the Socratic method to PKN subjects, it is known that there is an increase in learning outcomes from cycle I to cycle II. In cycle I, the average student learning outcomes are 69 in the moderate category. While student learning outcomes in cycle II with an average of 76 or in the High category. The percentage of mastery learning obtained by students in the cycle is 63%, while in the second cycle it is 90%.